2011
DOI: 10.1002/fuce.201100070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ce‐Doping on the Electrical and Electrocatalytical Behavior of La/Sr Chromo‐Manganite Perovskite as New SOFC Anode

Abstract: The effect of cerium substitution on the electrical and electrochemical characteristics of a new anode material La0.75Sr0.25Cr0.5Mn0.5O3 (LSCM) was examined by synthesizing CexLa0.75–xSr0.25Cr0.5Mn0.5O3 for x = 0–0.375). From x = 0–0.25, the structure is rhombohedral (S.G. R‐3c), and with a higher cerium content (x = 0.375) it becomes cubic (S.G. Pm‐3m). These materials are stable in the operating conditions of an SOFC anode. CexLa0.75–xSr0.25Cr0.5Mn0.5O3 and LSCM materials are p‐type semi‐conductors. Cerium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…The reason should be attributed to the more oxygen vacancy formation resulting in the increase of the repulsive force between neighboring cations. 25 As shown in Fig. 1(b), the doping of Ni (#15 mol %) had no inuence on the formation of the pure perovskite structure in Asite decient materials with orthorhombic symmetry.…”
Section: Thermal Structural and Morphological Analysesmentioning
confidence: 88%
“…The reason should be attributed to the more oxygen vacancy formation resulting in the increase of the repulsive force between neighboring cations. 25 As shown in Fig. 1(b), the doping of Ni (#15 mol %) had no inuence on the formation of the pure perovskite structure in Asite decient materials with orthorhombic symmetry.…”
Section: Thermal Structural and Morphological Analysesmentioning
confidence: 88%
“…It has been shown that the modification of Ce could effectively suppress the formation of carbon deposition at the Ni/YSZ anode [6]. It was also reported that significant improvement in electrochemical properties could be obtained by A-site substitution with Ce for LSCM [7]. Therefore, the investigation of the effect of Ce dopant in La 0.75 Sr 0.25 Fe 0.5 Cr 0.5 O 3-d on electrochemical performance and resistance against carbon deposition appears to be a promising research field.…”
Section: Introductionmentioning
confidence: 99%
“…Fe 3+ (ionic radius: 0.645 Å) ions are partially reduced to Fe 2+ with a larger ionic radius of 0.78 Å, and this causes an increase in the bond lengths and cell volume. At the same time, more oxygen vacancies are formed in LSFN and LSFNP upon reduction; this causes increased repulsive forces between neighboring cations, which could also contribute to cell expansion . However, Fe 0 metallic exsolutions on the surface of LSFN after reduction were confirmed in our previous report, and Pd nanoparticles are easy to exsolve from the perovskite‐oxide lattice under a reducing atmosphere .…”
Section: Resultsmentioning
confidence: 99%